Evaluation of the potential of total proanthocyanidin content in feces as an intake biomarker. (July 2021) - Magdaleno-Tapia, Cristina; Quifer-Rada, Paola; Rodríguez-Rodríguez, Elena; Estévez-Santiago, Rocío; Waterhouse, Andrew L.; Lamuela-Reventós, Rosa M.; Olmedilla-Alonso, Begoña; Pérez-Jiménez, Jara
Graphical abstract: Highlights: Porter method was modified to measure total proanthocyanidins (PAs) in feces. Total fecal PAs were evaluated as biomarker of PA intake. Total fecal PAs were associated with PA intake in supplementation preclinical study. Total fecal PAs were not associated with PA intake in an observational study. Abstract: Due to the health benefits associated with proanthocyanidins (PAs), it is useful to identify dietary PA biomarkers that can be determined by simple methods. Since increased levels of circulating PA metabolites are associated with increased fecal PA content, this study explores the spectrophotometric measurement of fecal PA content and its use as a biomarker of PA intake. To this end, fecal PA content was measured using an adaptation of Porter's spectrophotometric method in samples from a preclinical study and an observational study. In the former, excretion of 250–400 mg PA polymer equivalents/100 g feces was observed during supplementation and the day after, together with a significant association ( p  < 0.05) between PA intake and the excretion of both intact PAs and some PA metabolites, i.e., (+)-catechin, (−)-epicatechin and syringic acid. No relationship between intake and excretion was found in the observational study, either for the entire group (mean excretion of 240 ± 226 mg PA polymer equivalents/100 g feces) or after stratification into tertiles of consumption. In conclusion, the spectrophotometric determination of total PA content in feces proved to be a valid compliance marker in a preclinical study, but it was not associated with PA intake in free-living subjects. The potential of total PA excretion in observational studies, determined in fecal samples collected the day before dietary recall or in several fecal samples from the same subject, remains to be elucidated, as does a complete validation of the method proposed here.